The effect of Yeast Strain, Grape Solids, Nitrogen and Temperature on Fermentation Rate and Wine Quality - Tromp, A (South African Journal of Enology and Viticulture, 2017)
The effect of four yeast strains, two levels of grape solids, two nitrogen levels and three fermentation temperatures viz. 10°, 13° and 15° C on total fermentation time (TFT) and wine quality was studied in a factorial experiment by employing a nitrogen deficient Chenin blanc must. It was found that the presence of solids, addition of nitrogen and fermenting at 15° C decreased TFT dramatically. Nitrogen was the only factor which also increased wine quality, the other two having a detrimental effect. At optimum levels of nitrogen, yeast strains WE 452 and WE 500 (VORI collection) reduced TFT without detrimentally affecting wine quality. In the case of WE 452, no solids should be present and fermentation conducted at 10° C -13° C, and in the case of WE 500, traces of solids should be present and a fermentation temperature of between 13° C - 15° C should be utilized. Under these conditions WE 452 and WE 500 reduce TFT from C.76 days to as few as C.30 and C.15 days respectively.